Monitoring the Dynamics of T cell Clonal Diversity using Recombinant Peptide:MHC Technology - Blanchfield, J. Lori; Shorter, Shayla K.; Evavold, Brian D. (Frontiers in Immunology, 2013)
The capacity to probe antigen specific T cells within the polyclonal repertoire has been revolutionized by the advent of recombinant peptide:MHC (pMHC) technology. Monomers and multimers of peptide: MHC molecules can enrich for and identify antigen specific T cells to elucidate the contributions of T cell frequency, localization and T cell receptor (TCR) affinity during immune responses. Two-dimensional (2D) measurements of TCR-pMHC interactions are at the forefront of this field because the biological topography is replicated such that TCR and pMHC are membrane anchored on opposing cells, allowing for biologically pertinent measures of TCR antigen specificity and diversity. 2D measurements of TCR-pMHC kinetics have also demonstrated increased fidelity, compared to the 3-dimensional surface plasmon resonance data, and are capable of detecting T cell affinities that are below the detection level of most pMHC multimers. Importantly, 2D techniques provide a platform to evaluate affinity and antigen specificity against multiple protein epitopes within polyclonal T cell populations directly ex vivo from sites of ongoing immune responses. This review will discuss how antigen specific peptide:MHC molecules, with a focus on 2D technologies, can be used as effective tools to evaluate the range of TCR affinities that comprise an immune response and more importantly how the breadth of affinities determine functional outcome against a given exposure to antigen. kin